Scientific approaches as a methodological basis for forming culture of managing the personnel of future managers - Popova, Hanna; Artiukhina, Marina (ScienceRise: Pedagogical Education, 2017)
In the article the scientific approaches have been analyzed, and the methodological basis for the formation of culture of personnel management in the process of professional training of future managers has been developed. It is proved that effectiveness of forming culture of managing the personnel of future managers is achieved through the introduction of the complex of pedagogical conditions in the professional training: enrichment of the content of training on personnel management with additional cultural-oriented topics; diversification of the process of professional training of future managers by active and interactive forms and methods of educational activities; promotion of the development of professionalism of the teaching staff in order to ensure the effectiveness of the process of forming culture of managing the personnel of future managers. It is established that the methodological foundations of the first pedagogical condition create cultural and competence approaches. For the second pedagogical condition, the methodological background is provided by the personality-activity approach. For the third pedagogical condition, the acmeological approach is methodologically grounded. It is proved that the scientific approaches form a unified methodological basis for the holistic process of forming culture of the personnel management through the implementation in the professional training of future managers of the complex of pedagogical conditions